Collectively Exhaustive Hybrid Triboelectric Nanogenerator Based on Flow‐Induced Impacting‐Sliding Cylinder for Ocean Energy Harvesting (Adv. Energy Mater. 3/2022). Issue 3 (21st January 2022) - Kim, Ji‐Seok; Kim, Junyoung; Kim, Jong‐Nam; Ahn, Junseong; Jeong, Jun‐Ho; Park, Inkyu; Kim, Daegyoum; Oh, Il‐Kwon
Abstract : Triboelectric Nanogenerators In article number 2103076, Daegyoum Kim, Il‐Kwon Oh and co‐workers develop an ocean energy harvester utilizing a triboelectric nanogenerator (TENG) coupled with an oscillating cylinder via fluid‐structure interactions for wireless monitoring of ocean environments. Collectively exhaustive hybrid TENGs can be used to greatly maximize ocean energy harvesting performance from a synergy between freestanding sliding and contact‐separation modes.